Ribose operon repressor (RbsR) contributes to the adhesion of Aeromonas hydrophila to Anguilla japonica mucus. Issue 4 (27th January 2017) - Lin, Guifang; Chen, Wenbo; Su, Yongquan; Qin, Yingxue; Huang, Lixing; Yan, Qingpi
Abstract: The characterization of adhesion between pathogenic bacteria and the host is critical. Pathogenic Aeromonas hydrophila was shown to adhere in vitro to the mucus of Anguilla japonica . To further investigate the adhesion mechanisms of A. hydrophila, a mini‐Tn 10 transposon mutagenesis system was used to generate an insertion mutant library by cell conjugation. Seven mutants that were impaired in adhesion to mucus were selected out of 332 individual colonies, and mutant M196 was the most severely impaired strain. National Center for Biotechnology Information (NCBI) blast analysis showed that mutant M196 was inserted by mini‐Tn 10 with an ORF of approximately 1, 005 bp (GenBank accession numbers KP280172). This ORF is predicted to encode a protein consist of 334 amino acid, which displays the highest identity (98%) with the RbsR of A. hydrophila ATCC 7966. Random inactivation of rbsR gene affected the pleiotropic phenotypes of A. hydrophila . The adhesion ability and the survival level of the rbsR gene mutant (M196) were attenuated compared with the wild‐type and rbsR complementary type. The findings of this study indicated that RbsR plays roles in the bacterial adhesion and intracellular survival of A. hydrophila . Abstract : A mini‐Tn 10 transposon mutagenesis system was used to generate an insertion mutant library by cell conjugation. Seven mutants that were impaired in adhesion to mucus were selected out of 332 individual colonies, and mutant M196 was the most severely impaired strain. rbsR gene contributes to the adhesion ability and the survival of Aeromonas hydrophila .